Invasive candidiasis in low birth weight preterm infants: risk factors, clinical course and outcome in a prospective multicenter study of cases and their matched controls - Barton, Michelle; O’Brien, Karel; Robinson, Joan L; Davies, Dele H; Simpson, Kim; Asztalos, Elizabeth; Langley, Joanne M; Le Saux, Nicole; Sauve, Reg; Synnes, Anne; Tan, Ben; de Repentigny, Louis; et al. (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background This multicenter prospective study of invasive candidiasis (IC) was carried out to determine the risk factors for, incidence of, clinical and laboratory features, treatment and outcome of IC in infants of birth weight <1250 g. Methods Neonates <1250 g with IC and their matched controls (2:1) were followed longitudinally and descriptive analysis was performed. Survivors underwent neurodevelopmental assessment at 18 to 24 months corrected age. Neurodevelopmental impairment (NDI) was defined as blindness, deafness, moderate to severe cerebral palsy, or a score <70 on the Bayley Scales of Infant Development 2nd edition. Multivariable analyses were performed to determine risk factors for IC and predictors of mortality and NDI. Results Cumulative incidence rates of IC were 4.2%, 2.2% and 1.5% for birth-weight categories <750 g, <1000 g, <1500 g, respectively. Forty nine infants with IC and 90 controls were enrolled. Necrotizing enterocolitis (NEC) was the only independent risk factor for IC (p = 0.03). CNS candidiasis occurred in 50% of evaluated infants, while congenital candidiasis occurred in 31%. Infants with CNS candidiasis had a higher mortality rate (57%) and incidence of deafness (50%) than the overall cohort of infants with IC. NDI (56% vs. 33%; p = 0.017) and death (45% vs. 7%; p = 0.0001) were more likely in cases than in controls, respectively. IC survivors were more likely to be deaf (28% vs. 7%; p = 0.01). IC independently predicted mortality (p = 0.0004) and NDI (p = 0.018). Conclusion IC occurred in 1.5% of VLBW infants. Preceding NEC increased the risk of developing IC. CNS candidiasis is under-investigated and difficult to diagnose, but portends a very poor outcome. Mortality, deafness and NDI were independently significantly increased in infants with IC compared to matched controls.